Mastering microsoft VBA - Hart-David, Guy (Wiley, 2005)
Mastering VBA is the quickest, easiest way to learn to use VBA programming to customize and improve Microsoft Office and hundreds of other VBA-enabled applications. Step-by-step instructions address both general techniques, suitable for any VBA host, and specific procedures for Word, Excel, PowerPoint, Access, and Outlook. This book covers the Office 2003 applications, but you can use it to program Office XP and Office 2000 as well.